Homotopy perturbation method for solving Caputo‐type fractional‐order Volterra‐Fredholm integro‐differential equations. Issue 5 (10th July 2019) - Das, Pratibhamoy; Rana, Subrata; Ramos, Higinio
Abstract : This work considers the solution of fractional Volterra‐Fredholm integro‐differential equations. Here, we consider the approximation of the solution based on semi‐analytical approaches. We use the homotopy perturbation method approach for this purpose. It is observed through different examples that the adopted strategy is not only an effective tool for approximation of the solution but also can lead to the exact solution of certain problems.